Efektivitas Minum Seduhan Daun Mint (Mentha Piperita) terhadap Frekuensi Emesis Gravidarum pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Harapan Raya Pekanbaru - Tri Fitri Angraini; Lisviarose Lisviarose; Wira Akdeni Aifa; Fatma Nadia (Pusat Riset dan Inovasi Nasional, 2026)
Data from the 2021 Indonesia Demographic and Health Survey (IDHS) showed that around 45% of pregnant women experienced emesis gravidarum, increasing to 58% in 2022. In Riau Province, the prevalence is also estimated at 58% and continues to rise annually. If left untreated, emesis gravidarum can negatively affect both maternal and fetal health. One alternative management strategy involves non-pharmacological therapies, particularly herbal remedies. This study aimed to assess the effectiveness of mint leaf infusion in reducing the frequency of emesis gravidarum among first-trimester pregnant women in the working area of Harapan Raya Public Health Center, Pekanbaru. The research applied a quantitative method with a quasi-experimental two-group pretest–posttest design. The sample included 30 first-trimester pregnant women experiencing emesis gravidarum, consisting of 15 respondents in the intervention group and 15 in the control group, selected using purposive sampling. Data were collected using the PUQE-24 questionnaire and analyzed through univariate and bivariate methods. The Shapiro–Wilk test revealed that the data were not normally distributed, leading to the use of the Wilcoxon Signed-Rank Test for further analysis. The findings demonstrated a significant decrease in the frequency of emesis gravidarum among participants who received mint leaf infusion therapy, while no significant change was found in the control group. Therefore, mint leaf infusion can be considered an effective, safe, and practical complementary therapy to help reduce emesis gravidarum symptoms during antenatal care services.